(untitled) (AYUSHDHARA, 2023)
Tamak Shwasa is a term that encompasses many diseases such as shortness of breath as the main symptom. But we can also associate bronchial asthma with Tamak Shwasa because of the remaining four, three of them are incurable and the fourth is Kshudra Shwasa, which is caused by overwork and overeating, it can be cured in a simple way. Early onset is easy to treat, but the chronic condition is difficult to treat. In Ayurveda, the word Shwasa defines its meaning as a disease in itself as well as symptoms and problems of other diseases. The patient has an attack of a disease that threatens his life. Acharya Charaka describes Tamak Shwasa as a Yappya type of illness in which the patient has to rely on medicine for relief. Acharya Charak teaches different good thoughts about Tamak Shwasa. Every Ayurvedic practitioner should have a detailed knowledge of Tamak Shwasa to distinguish between Chikitsa and disease assessment. In Pipalaadi leh therapy, 04 pts. i.e., 09.76% of the patients attained marked improvement, 33 pts. i.e., 80.48% of the patients attained moderate improvement and 04 pts. i.e., 09.76% of the patients attained mild improvement.